Medeni yargılama hukukunda davanın tamamen ıslahı - Sanıvar, Cüneyt (My University, 2019)
Tezimizin konusunu “Medeni Yargılama Hukukunda Davanın Tamamen Islahı” oluşturmaktadır. Hukuk Muhakemeleri Kanunu’na göre, taraflardan her biri, yapmış olduğu usul işlemlerini kısmen veya tamamen ıslah edebilir. Yani kanun metni tamamen ıslah ile kısmen ıslahı bir arada düzenlemiştir. Tezimizin konusunu davanın tamamen ıslahı oluşturmakla birlikte konunun daha iyi anlaşılması bakımından tezimizde yer yer kısmen ıslaha da değinilmiştir. Ayrıca bazı başlıklar bakımından ıslah müessesesi kısmen veya tamamen olarak ayrılmadan yani her iki kurumu da kapsayacak şekilde, genel olarak ıslah başlığı altında açıklanmıştır. Tezimizde davanın tamamen ıslah ise tüm detaylarıyla örneklendirilerek ve Yargıtay kararlarıyla desteklenerek işlenmiştir.Bu bağlamda tezimiz dört ana bölümden oluşmaktadır. Birinci bölümde, ıslahın tanımı, hukuki niteliği, kapsam ve amacı, ıslah kurumunun Medeni Usul hukukundaki ilkelerle bağlantısı, benzer kurumlarla karşılaştırılması ve ıslah kurumuna yeni Kanun ile getirilen değişikliklere değinilmiştir. İkinci bölümde, ıslah kurumu ile iddia ve savunmanın değiştirilmesi veya genişletilmesi yasağı arasındaki ilişki, ıslahın konusu ve çeşitleri, davanın tamamen ıslahı ve bu yola başvurabilecek kişiler konularına değinilmiştir. Üçüncü bölümde ise, tamamen ıslahın yapılma zamanı, uygulamada davanın tamamen ıslahı, ıslahın mümkün olmadığı durumlar ile ıslahı gerektirmeyen durumlar başlıkları incelenmiştir. Son olarak dördüncü bölümde de tamamen ıslah ve zamanaşımı arasındaki ilişki, tamamen ıslahın etkisi ve sonuçları, tamamen ıslahtan dönme ve kötü niyetli ıslah konularına değinilmiştir.

The subject of our thesis is “Complete Amendment of the Case in Law of Civil Procedure”. According to the Code of Civil Procedure, each of the parties may, in whole or in part, amend the procedural proceedings. In other words, amendment and partly amendment regulated together by the text of law. Although the subject of our thesis constitutes the complete amendment of the case, in order to better understand the subject, it has been mentioned in some places in the thesis. In addition, in terms of some titles, the institution of amendment has been described under the heading of amendment in general, in part or completely without leaving it, ie covering both institutions. In our thesis, the complete amendment of the case is illustrated with all the details and supported by the Supreme Court decisions.In this context, our thesis consists of four main chapters. In the first part, the definition, legal quality, scope and purpose of the amendment, the connection of the amendment institution with the principles in the Civil Procedure Law, its comparison with similar institutions and the amendments brought to the correctional institution by the new Law are mentioned. In the second part, the relationship between the amendment institution and the prohibition of changing or expanding the claim and defense, the subject and types of ammendment, the complete ammendment of the case and the persons who can apply this way are discussed. In the third part, the time of complete ammendment, the complete ammend of the case in practice, the situations in which amendment is not possible and the situations that do not require amendment are examined. Finally, in the fourth chapter, the relationship between complete amendment and prescription, the effect and results of complete amendment, return from complete amendment and malicious amendment are discussed.
Keywords: Civil law; Complete Amendment; Davacı Amendment; Hukuk; Islah; Law; Law of Civil Procedure; Medeni hukuk; Medeni Usul Hukuku; Prosecuter; Tamamen Islah